Examining the edges of multi-layer graphene sheets - Warner, J; Schäffel, F; Rümmeli, M; Büchner, B (2009)
Multi-layer graphene (MLG) sheets were produced from highly ordered pyrolytic graphite by mechanical exfoliation. We use aberration-corrected, low-voltage, high-resolution transmission electron microscopy to study the atomic structure at the edges of the sheets. In general, we find two different types of edges of MLG sheets are produced, either parallel to a zigzag direction or an arm-chair direction. A MLG sheet with edges parallel to the zigzag direction was observed to have small random corrugations and was relatively straight. We observed edges parallel to the arm-chair direction with highly corrugated atomic structure and terracing. We show that the corrugations are due to sawtooth oscillations in the atomic structure with zigzag edge terminations along the general arm-chair direction. © 2009 American Chemical Society.